Peran Hardiness Sebagai Moderator Fear of Failure Terhadap Intensi Berwirausaha Pada Mahasiswa Universitas Negeri Makassar - Fauziah Nurhidayah; Dian Novita Siswanti; Syamsul Bachri Thalib (CV. Ulil Albab Corp, 2024)
This research is a quantitative study to determine the role of hardiness in moderating the influence of fear of failure on the entrepreneurial intentions of Makassar State University students. Participants in this research were 335 Makassar State University students, Class of 2023. This research uses the Intrinsic Entrepreneurial Intention Questionnaire (EIQ) to measure Entrepreneurial Intention, the Performance Failure Appraisal Inventory (PFAI) scale to measure Fear of Failure, and the Personal Views Survey III-R scale to measure Hardiness. Analysis of this research data using moderation analysis through the process model developed by Hayes (2018) to see the moderating role of hardiness in seeing the relationship between fear of failure and students' entrepreneurial intentions. The research results show that there is a negative influence between fear of failure on entrepreneurial intentions (β=-0.127, t=-5.925, p<0.05). This shows that an increase in fear of failure is followed by a decrease in entrepreneurial intentions, and vice versa. Meanwhile, hardiness has a positive effect on entrepreneurial intentions (β=0.164, t=4.506, p<0.05). This shows that an increase in hardiness is also accompanied by an increase in entrepreneurial intentions. However, there was no moderating role of hardiness in the relationship between fear of failure and students' entrepreneurial intentions (β=-0.003, t=-1.100, p>0.05).